7(4+h)=13h

Simple and best practice solution for 7(4+h)=13h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(4+h)=13h equation:


Simplifying
7(4 + h) = 13h
(4 * 7 + h * 7) = 13h
(28 + 7h) = 13h

Solving
28 + 7h = 13h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-13h' to each side of the equation.
28 + 7h + -13h = 13h + -13h

Combine like terms: 7h + -13h = -6h
28 + -6h = 13h + -13h

Combine like terms: 13h + -13h = 0
28 + -6h = 0

Add '-28' to each side of the equation.
28 + -28 + -6h = 0 + -28

Combine like terms: 28 + -28 = 0
0 + -6h = 0 + -28
-6h = 0 + -28

Combine like terms: 0 + -28 = -28
-6h = -28

Divide each side by '-6'.
h = 4.666666667

Simplifying
h = 4.666666667

See similar equations:

| sin(2x-60)=-cos(3x) | | 121=-11b | | 5p-7=2p | | 90-x=0.8(x) | | 1/2d-12 | | 83=-3(6b+3)+2 | | x^2+y^2+8y=9 | | 40-10x=40+2x | | 11x+12=265 | | 2m-3n=1 | | 33=-5-2x | | (2x-5)=(45) | | 2x-5+45+80+105=360 | | 2/9x1/8= | | (d+2)*(d+2)=8 | | 8x+28-4x=20 | | 4a(a-1)=15 | | 8-(5x+3)=13-7x | | Secx=3/7 | | -8y+16=16 | | 4n=252 | | 2x-9x=-22x+5x+25 | | 26p=572 | | 34=7x-8 | | 3x-6y=-6x+5y | | 5x^2+30x+2=0 | | 2x^2+22x+196=0 | | 10x^2-28x=48 | | 4a^2b/2ab | | x(2x+3)=2 | | 4ln-9b=12 | | 5p−2=3/4 |

Equations solver categories